Tattoo-less chest wall and regional nodal irradiation using surface imaging - Boris Mueller; Yulin Song; Xingchen Zhai; Yubei Liang; Paul Tamas; Simon Powell; David M Guttmann; Diana Roth O’Brien; Beryl McCormick; Atif Khan; Laura Cervino-Arriba; Bo Zhao; et al. (Technical Innovations & Patient Support in Radiation Oncology)
Purpose/Objective: Skin tattoos represent the standard for surface alignment and setup of breast cancer radiotherapy yet contribute to adverse cosmesis and patient dissatisfaction. With the advent of contemporary surface imaging technology, we evaluated setup accuracy, time, and dosimetric parameters between traditional tattoo-based setup techniques and a “tattoo-less” approach for lymph node positive and high-risk breast cancer patients requiring chest wall and regional nodal radiation.Material/MethodsPatients receiving chest wall radiation for breast cancer underwent a traditional tattoo-based setup (TTB), alternating daily with a tattoo-less setup via surface imaging using AlignRT (ART) to serve as an internal control. Following initial setup (using tattoos or AlignRT), target position was verified by daily kV imaging, with matching on the chest wall bony anatomy representing ground truth. Translational (TS) and rotational shifts (RS) were ascertained, as were setup time and total in-room time. Delivered dosimetry was calculated using the reverse isocenter shift technique. Statistical analyses used the Wilcoxon Signed Rank test and Pitman-Morgan variance test. Results: A total of 49 breast cancer patients receiving a total of 1118 fractions (n = 560 for ART and 558 for TTB) of chest wall radiation were analyzed. For tattoo-less setup via ART, the median absolute TS was 0.28 cm vertical (range: 0.14–––0.48), 0.24 cm lateral (0.10–––0.40), and 0.26 cm longitudinal (0.13––0.44). For TTB setup, the corresponding median TS were 0.34 cm (0.15–––0.52), 0.29 (0.13–––0.46), and 0.34 cm (0.14–––0.59), respectively. ART was significantly more accurate than TTB with regard to TS (p = 0.038, 0.007, <0.001, respectively). Variance testing also showed increased precision with ART in the vertical (p < 0.001) and longitudinal (p < 0.001) axes.The median absolute RS for ART was 0.80° rotational (range:0.40–1.50), 0.60° roll (0.20–1.20), and 0.50° pitch (0.10–1.00). The corresponding median RS for TTB was 1.00° (0.40–1.70), 0.60° (0.20–1.20), and 0.50° (0.10–1.00). ART was significantly more accurate for RS than TTB (p = 0.023). ART setup was otherwise not statistically different from TTB regarding roll and pitch (p = 0.558, 0.929, respectively). ART showed no difference in precision versus TTB regarding RS, pitch, and roll (p = 0.181, p = 0.544, p = 0.858).The median total in-room time for ART was 18.77 min (range: 16.04–20.77) and 18.70 min (17.58–20.67) for TTB (p = 0.38). The median setup time was 12.75 min (11.43–14.80) for ART and 13.78 min (12.42–15.09) for TTB (p = 0.054). There was no significant difference between the AlignRT and the tattoo-based methods for both setup and in-room time. Conclusion: These findings indicate that utilizing the tattoo-less setup method with AlignRT provides sufficient accuracy and speed to potentially supplant the use of surface tattoos in lymph node positive and high-risk breast cancer patients requiring chest wall and regional lymph node radiation. Further investigations involving larger patient cohorts will further inform whether surface imaging can wholly replace tattoo-based approaches.